Hubungan Kadar Kreatinin Serum dengan Kadar Gula Darah Puasa pada Pasien Diabetes melitus Tipe 2 di RSUD Dr.Sayidiman Kabupaten Magetan - Mahara, Nanda Dwi (2016)
Background : Diabetes mellitus (DM) is a metabolic disease with characterized hyperglycemic due to abnormalities insulin secretions, insulin performance, or both of them. In Indonesia, the prevalence of diabetes mellitus in every year is increased. Type 2 diabetes mellitus is a chronic disease which can cause complications such as diabetic nephropathy. The state of diabetic nephropathy is a kidney damage that is often found in patients with diabetes mellitus. One examination of kidney function is by measuring serum creatinine levels. Objective : The objective of this research to determine the relations between serum creatinine levels with fasting plasma glucose levels in patients with type 2 diabetes mellitus . Method : This observational research used cross-sectional method. Samples were determined by purposive sampling with 36 samples. Data were analyzed by correlation test Rank Spearman. Result : The result of correlation test Rank Spearman showed positive correlation between serum creatinine levels with fasting plasma glucose levels (p<0.001, r = 0.741). Conclusion : There is a positive correlation between serum creatinine levels with fasting plasma glucose levels in type 2 diabetes mellitus patients. The higher fasting blood sugar levels can cause the higher serum creatinine levels.